How does climate exacerbate root causes of conflict in Mali? An impact pathway analysis - Madurga Lopez, Ignacio M.; Dutta Gupta, Tanaya; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Mali, using an impact pathway analysis. Three main impact pathways are identified: 1) Resource availability and livelihood insecurity ; 2) Farmer-herder conflict in the Inner Niger Delta; 3)Mobility and resource competition in the South.